2011
DOI: 10.1007/s11664-011-1514-3
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Thermoelectric Properties of Co4Sb12-Based Skutterudites with Multiple Filler Atoms: Ce0.1In x Yb y Co4Sb12

Abstract: Void-filling in the CoSb 3 skutterudite lattice with different kinds of heavy elements has proven to be an effective mechanism to enhance thermoelectric performance due primarily to a reduction in lattice thermal conductivity. Specifically, our findings on the series In x Yb y Co 4 Sb 12 [0 £ (x, y) £ 0.2] have further motivated an attempt to form triple-filled skutterudites Ce 0.1 In x Yb yCo 4 Sb 12 with In and Yb concentrations [0 £ (x, y) £ 0.2] and with the Ce concentration held constant (Ce 0.1 ). All of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 18 publications
(18 reference statements)
1
30
0
Order By: Relevance
“…16 Even further reductions have been reported in multi-filled compounds where two or more elements are used as rattler atoms. 7,[17][18][19][20][21][22][23][24] The larger reductions in the thermal conductivity in the thermal conductivity of multi-compared to single-filled materials is attributed to the scattering of a broader range of host lattice phonon frequencies due to the rattlers of the different elements vibrating at different frequencies. In a recent contribution 25 on the study of rattling in the Al-doped β-pyrochlores, AAl0.33W1.67O6 (A = K, Rb, Cs), we reported the discovery of novel rattling of K atoms in KAl0.33W1.67O6 involving both vibrations at a broad range of frequencies as well as local diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…16 Even further reductions have been reported in multi-filled compounds where two or more elements are used as rattler atoms. 7,[17][18][19][20][21][22][23][24] The larger reductions in the thermal conductivity in the thermal conductivity of multi-compared to single-filled materials is attributed to the scattering of a broader range of host lattice phonon frequencies due to the rattlers of the different elements vibrating at different frequencies. In a recent contribution 25 on the study of rattling in the Al-doped β-pyrochlores, AAl0.33W1.67O6 (A = K, Rb, Cs), we reported the discovery of novel rattling of K atoms in KAl0.33W1.67O6 involving both vibrations at a broad range of frequencies as well as local diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…6 In was also observed in the form of secondary phase InSb, and therefore assumed as not entering entirely as ller atoms in In x Yb y Co 4 Sb 12 with solubility limit of In less than x ¼ 0.20 (ref. 7) and in In x Ce y Co 4 Sb 12 with solubility limit of In less than x ¼ 0.15.…”
Section: Introductionmentioning
confidence: 96%
“…A series of In-filled skutterudites of various groups prepared with various methods followed and confirmed that indium was useful as a filler. These investigations were extended to double-filled skutterudites of In with Sn [29], with Ba [3,16,[30][31][32][33][34][35][36][37], with Tl [38], with Pb [35], with Ce [6,[39][40][41][42], with Pr [27], with Nd [21,43], with Yb [7,8,16,19,[44][45][46][47][48][49], with Lu [50], and to triple filled skutterudites of In with Ba and Ce [51], with Ba and Yb [16,52], with La and Yb [47], with Ce and Yb [41,42,53] and Ga and Tl [26]. There are also attempts to improve the TE properties by doping and/or alloying e.g.…”
Section: Introductionmentioning
confidence: 99%